MRSA USA300 at Alaska Native Medical Center, Anchorage, Alaska, USA, 2000–2006 - David, Michael Z. (Centers for Disease Control and Prevention, 2012)
To determine whether methicillin-resistant Staphylococcus aureus (MRSA) USA300 commonly caused infections among Alaska Natives, we examined clinical MRSA isolates from the Alaska Native Medical Center, Anchorage, during 2000–2006. Among Anchorage-region residents, USA300 was a minor constituent among MRSA isolates in 2000–2003 (11/68, 16%); by 2006, USA300 was the exclusive genotype identified (10/10).